2015
DOI: 10.1515/joc-2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization of 45-Channel Superdense Wavelength-Division-Multiplexed (SDWDM) Optical Add–Drop Multiplexer (OADM) Ring Network

Abstract: In this paper, performance analysis of high-speed superdense wavelength-division-multiplexing (SDWDM) optical add-drop multiplexer (OADM) optical ring network for 6 nodes, 45 wavelengths having channel spacing of 0.2 nm on 300 km unidirectional nonlinear single-mode fiber ring of 10 Gbit/s has been reported. The performance optimization of the system by comparing different modulation formats has been reported on the basis of eye diagram and bit error rate (BER). It has been reported that CSRZ modulation format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, such a topology has a poor performance in the reliability and the flexibility of adding or removing network nodes. When using the current network architecture whilst considering the cost of equipment build-up, some researchers have suggested that a mixed tree and ring network architecture may be a reasonable solution [ 8 ]. In a ring-shaped architecture, considering scalability and system reliability is necessary; thus, the optical add/drop multiplexer (OADM) is a good choice [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, such a topology has a poor performance in the reliability and the flexibility of adding or removing network nodes. When using the current network architecture whilst considering the cost of equipment build-up, some researchers have suggested that a mixed tree and ring network architecture may be a reasonable solution [ 8 ]. In a ring-shaped architecture, considering scalability and system reliability is necessary; thus, the optical add/drop multiplexer (OADM) is a good choice [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%